A new perspective on positive symptoms: expression of damage or self-defence mechanism of the brain? - Annibale Antonioni; Emanuela Maria Raho; Mariachiara Sensi; Francesco Di Lorenzo; Luciano Fadiga; Giacomo Koch (2024)
Abstract Usually, positive neurological symptoms are considered as the consequence of a mere, afinalistic and abnormal increase in function of specific brain areas. However, according to the Theory of Active Inference, which argues that action and perception constitute a loop that updates expectations according to a Bayesian model, the brain is rather an explorer that formulates hypotheses and tests them to assess the correspondence between internal models and reality. Moreover, the cerebral cortex is characterised by a continuous “conflict” between different brain areas, which constantly attempt to expand in order to acquire more of the limited available computational resources, by means of their dopamine-induced neuroplasticity. Thus, it has recently been suggested that dreams, during rapid eye movement sleep (REMS), protect visual brain areas (deprived of their stimuli during rest) from being conquered by other normally stimulated ones. It is therefore conceivable that positive symptoms also have a functional importance for the brain. We evaluate supporting literature data of a ‘defensive’ role of positive symptoms and the relevance of dopamine-induced neuroplasticity in the context of neurodegenerative and psychiatric diseases. Furthermore, the possible functional significance of idiopathic REMS-related behavioural disorder as well as phantom limb syndrome is examined. We suggest that positive neurological symptoms are not merely a passive expression of a damage, but active efforts, related to dopamine-induced plasticity, to maintain a correct relationship between the external world and its brain representation, thus preventing healthy cortical areas from ousting injured ones.